COMPARISON OF ENDOTRACHEAL INTUBATION VERSUS SUPRAGLOTTIC AIRWAY DEVICE IN PATIENTS UNDERGOING CORNEAL TRANSPLANTATION UNDER GENERAL ANAESTHESIA - Abbas, Sana; Zafar, Omar; Abbas, Beenish; Mehmood, Basit; Hayat, Umer; Javaid, Hassaan (Pakistan Armed Forces Medical Journal, 2021)
Objective: To compare endotracheal intubation versus Suraglottic airway device in patients undergoing penetrating keratoplasty under general anaesthesia.Study Design: Quasi-experimental study.Place and Duration of Study: Armed Forces Institute of Ophthalmology, Rawalpindi, from Jan 2018 to Mar 2020.Methodology: Total 28 patients enrolled with a mean age of 42.82 ± 7.86 years and age-range of 18-55 belonging to American Society of Anesthesiology I, II & III undergoing penetrating keratoplasty under general anaesthesia. The airway was secured with I–Gel and Endotracheal tube in group A (n=14) and group B (n=14) respectively. Pre anaesthesia assessment along with informed written consent performed. General Anesthesia is given and patients monitored as per standard protocols. Postextubation incidence of cough, sore throat, bronchospasm, stridor and blood on device recorded in addition to surgery and recovery duration.Results: Twenty-eight patients were enrolled in the study with a mean age of 42.82 ± 7.86 years. There were 9 (32.1%) females and 19 (67.9%) males in the study group. The recovery time was significantly lower for group A as compared to group B (72.64 ± 5.06 vs 80.43 ± 3.75, p